KREATIVITAS NAMIN DALAM PETA PERKEMBANGAN JAIPONGAN BAJIDORAN - Atang Suryaman (Paraguna, 2018)
The  game   ofkendangin  each  typeofperfonnance  art  has  its  own  peculiarities. First  in  the  context   ofkendangaspartofindependentkarawitanwork,  then  the secondin  the  kendangcontext   as  partofthefunctional  karaokework  which   is specificallyin  dance   music.  Each  player  and  drum  game   has  its  ownspecificity and  capabilities,  sothedrummeris  apersonwhois  required  tohave  specialskills. Especially  inperfonnance  artthat  requires  the  ability  todo  renewal,  development and  creativity.  Oneofthem  isintheartofBajidoran-Jaipongan,  where  inaddition to  being  united   in  karawitan,  at  the  same   time  itis  required   toserve   a  dancer (Bajidor).  From  a  series  ofkendangplayers  and  Bajidorangroups  that  are  well knowninthe  community,  the  name  Namin  and  "NaminGrup"areamong  the  most calculated.   From   various   perspectives,   especially  from   the   point  of  view   of observersand  actors,Namin  was  notonly  known  as  along-standingartistinthe performing  arts  world,  but  also  known  forhis  creativity.  In  the  development  of Bajidoran  -  Jaipongan,  the  term  "GaaNamin"  is  known,  itshows  a  distinctive pattern  that   is  identical  to  the  drum  game   created   by  Namin.  Tofind  out  the backgrounduntilfinallyNamin  isable  todisplaythe  distinctivedrum,then  Namin needsto  be  seenas  apersonwho  has  a  background  that  cannot  be  separated from  theprocessofart,  including  the  environmentand  the  carrying  capacity  itself From  thesevarious   dimensions,  Namin  is  a  creativefigureas  the  definition  ofa creative   figure  is   mentioned   as   a   unique   person  who    can   respond   to   his environment.  And   through   its  work   that   has   exceeded  the   40-year  mark   with Namin  Group,  ifNamin  has  notonly  demonstratedcreativity  inthe  artworld,  but alsoshowedconsistency,  simplicity,  and  leadershipspiritincarrying  outhis  work towardstheworld  heloves  most,  Bajidoran.